Optimization of E-Bupot Use in Increasing the Effectiveness and Efficiency of Tax Deduction/ Collection by Village Government X, Sumenep Regency - Yandari, Aprilya Dwi; Moh.Faisol; Isnani Yuli Andini; Kwartatmono, Djoko Nestri (Indonesian Journal of Society Development, 2024)
With such rapid development, all economic activities must begin to adapt to all existing changes. Our country's taxation system, which was originally carried out manually, has now been implemented with digitalization, one of which is E-Bupot. The problem currently faced is the lack of understanding in the process of using E-Bupot. In addition, local village officials also lack understanding regarding the taxation system and procedures. The Community Service Team aims to provide direction for socialization and assistance so that later partners will be able to use E-Bupot Unification to increase the effectiveness and efficiency of tax collection and deductions. This activity uses methods including the team conducting surveys, pre-research, socialization and assistance for E-Bupot Unification. This activity by the Community Service Team has a very positive impact on users where they are able to archive data where the archive is very much needed in order to be able to account for the existing data to the manager or the next party. The sustainability of this service is also expected that the local village office can use the taxation system properly